Waste for building material production as a method of reducing environmental load and energy recovery - Latosińska, Jolanta; Gawdzik, Jarosław; Honus, Stanislav; Orman, Łukasz J.; Radek, Norbert (Frontiers in Energy Research, 2023)
Proper treatment and recycling of waste is crucial for the natural environment. Biowaste and ash might be used for ceramic building materials production. Reduction in the amount of waste leads to the smaller burden on the environment and it can also offer recovery of energy. The paper presents the results of an experimental study of compressive strength of samples made from clay with waste additives: ash and sewage sludge. It was proven that the increasing amount of the waste materials decreases strength properties in all incineration temperatures. SEM analysis was used to determine the internal structure of the samples. Tests of heavy metals' leaching revealed that concentration of copper, chromium, nickel and zinc in leachate generally decreased with increasing sintering temperature. Moreover, the level of chromium was observed to exceed the permissible level.